Distribution of biomass dynamics in relation to tree size in forests across the world. Issue 5 (24th February 2022) - Piponiot, Camille; Anderson‐Teixeira, Kristina J.; Davies, Stuart J.; Allen, David; Bourg, Norman A.; Burslem, David F. R. P.; Cárdenas, Dairon; Chang‐Yang, Chia‐Hao; Chuyong, George; Cordell, Susan; Dattaraja, Handanakere Shivaramaiah; Duque, Álvaro; et al.
Summary: Tree size shapes forest carbon dynamics and determines how trees interact with their environment, including a changing climate. Here, we conduct the first global analysis of among‐site differences in how aboveground biomass stocks and fluxes are distributed with tree size. We analyzed repeat tree censuses from 25 large‐scale (4–52 ha) forest plots spanning a broad climatic range over five continents to characterize how aboveground biomass, woody productivity, and woody mortality vary with tree diameter. We examined how the median, dispersion, and skewness of these size‐related distributions vary with mean annual temperature and precipitation. In warmer forests, aboveground biomass, woody productivity, and woody mortality were more broadly distributed with respect to tree size. In warmer and wetter forests, aboveground biomass and woody productivity were more right skewed, with a long tail towards large trees. Small trees (1–10 cm diameter) contributed more to productivity and mortality than to biomass, highlighting the importance of including these trees in analyses of forest dynamics. Our findings provide an improved characterization of climate‐driven forest differences in the size structure of aboveground biomass and dynamics of that biomass, as well as refined benchmarks for capturing climate influences in vegetation demographic models. Abstract : See also the Commentary on this article by Zuidema & van der Sleen, 234 : 1544–1546 .